Numerical Methods for Fluid-Structure Interaction - A Review (Communications in Computational Physics, 2020)
The interactions between incompressible fluid flows and immersed structures are nonlinear multi-physics phenomena that have applications to a wide range ofscientific and engineering disciplines. In this article, we review representative numerical methods based on conforming and non-conforming meshes that are currently available for computing fluid-structure interaction problems, with an emphasis on some ofthe recent developments in the field. A goal is to categorize the selected methods andassess their accuracy and efficiency. We discuss challenges faced by researchers in thisfield, and we emphasize the importance of interdisciplinary effort for advancing thestudy in fluid-structure interactions.